(untitled) (Dimensión Antropológica, 2019)
In the region known as La Montaña of Guerrero, Mexico, agricultural rites are carried out at sacred sites related to the mountain and rain deity. There the people build altars to Saint Mark, a dual deity; the Holy Cross or cross of hill, with stronger pre-Hispanic than Christian affiliations, is also venerated. The orientation of the altars in relation to the cardinal directions, gives the offerings specific meanings. An important aspect of the altars among the Me phaa’ (Tlapanec) and Na savi ethnic groups is the presence of offerings in counted bundles, which imply cultural continuities. Another of these continuities among the Nahuas and Me phaa’ is the existence of sacred bundles (teotl among the Nahuas; saku’ among the Mephaa’), as well as tamales, called tzoalli among the Nahuas. The aim of this article is to outline the configuration of these sacred spaces.